2014
DOI: 10.1016/j.mjafi.2014.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different regimes of misoprostol for the termination of early pregnancy failure

Abstract: Early pregnancy failure a b s t r a c tBackground: Nearly 20% of all confirmed pregnancies end in spontaneous abortion. Misoprostol's use in early pregnancy failure is varied and dose and route are not well established. The aim of this study was to compare the efficacy and the side effects of different regimes of misoprostol in causing expulsion of products of conception in early pregnancy failure.Method: Women patients with an ultrasound diagnosis of early pregnancy failure, less than 12 weeks gestation were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…A single dose of 800 micrograms of misoprostol by vaginal or oral for missed abortion was recommended by National Institute for Health and Care Excellence (NICE) 20 . However some studies reported converse opinion, by pointing out that a lower dose or different routes of misoprostol may be equally effective 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%
“…A single dose of 800 micrograms of misoprostol by vaginal or oral for missed abortion was recommended by National Institute for Health and Care Excellence (NICE) 20 . However some studies reported converse opinion, by pointing out that a lower dose or different routes of misoprostol may be equally effective 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%
“…7 Early pregnancy failure is common, occurring in 15-20% of known pregnancy. 5 Termination of early pregnancy failure can be achieved by expectant management, surgical evacuation or medical management. 4 There is no definite protocol with evidence-based efficacy, safety and acceptability for termination of eary pregnancy failure in woman with a scarred uterus.…”
Section: Discussionmentioning
confidence: 99%
“…4 However the appropriate dose and route of administration are not welldetermined. 5 Here we present a case of first trimester ruptured uterus in a woman with a scarred uterus after induced abortion with mifepristone and misoprostol.…”
Section: Introductionmentioning
confidence: 97%
“…7 Early pregnancy failure is common, occurring in 15-20% of known pregnancies. 5 It is a perplexing complication especially in women with previous uterine surgery. Termination of early pregnancy failure can be achieved through expectant management, surgical evacuation, or medical management.…”
Section: Discussionmentioning
confidence: 99%
“…4 However, the appropriate dose and route of administration is not well-determined. 5 Here, we present a case of a first…”
Section: Introductionmentioning
confidence: 99%